Delicious but Immoral? Ethical Information Influences Consumer Expectations and Experience of Food - Armstrong, Beth; Meskin, Aaron; Blundell-Birtill, Pam (Frontiers in Psychology, 2019)
It has been suggested that information about ethically relevant factors in production can affect both the expectation and experience of foods. However, evidence on these issues is inconsistent. We begin by discussing recent philosophical work on the interaction of ethical and aesthetic values in the domain of food, work which is inspired by a similar debate about art. Some philosophers have suggested that ethical factors in production that leave a ‘trace’ on a product, i.e., make a perceivable difference to it, will affect the aesthetic quality of the food. There has also been the suggestion that these sorts of ethical/aesthetic interactions may vary across different kinds of food. In two studies we examined the expected experience and the actual experience of eating various foods, when participants had been given ethically relevant information about those foods. We examined people’s ethical values and the effect that had on the ratings. We found strong evidence to suggest that ethically relevant information affects expected experience of food and that the valence of the information is a significant factor. We found an effect of ethical values on expectations of food. Most notably, we found evidence that suggests that ‘trace’ may be a relevant factor mediating the effect of ethically relevant information on expectations and experience of food. Future research should further explore the factor of trace, look at the effect of ethical information in a wider range of foods, and investigate these phenomena in distinct populations.